Free pages and other essays : anarchist musings - González Prada, Manuel, 1844-1918 (Library of Latin America., 2003)
"Manuel Gonzalez Prada (1844-1918) was one of the leading intellectual and literary figures of Peru. His reputation as an essayist extended beyond national boundaries. At home these essays, along with his potent speeches, influenced generations of young radicals. A powerful political reformer, he founded the Party of National Unity in 1891, was linked to the anarchist movement, and served as Director of the National Library from 1912-1914." "His writings have had enormous impact on the literary and political life of Peru: taking up the defense of exploited indigenous people, broadsiding the landowning oligarchy, and denouncing the social and political errors of the country. In fact, the radical politics Prada advocated then are still alive and relevant today: Modernization (secularization) of Peru, transformation of a nation through its people, promotion of internationalism (universalism) versus overt patriotism (communitarianism), and condemnation of war." "This translation is based on the Obras of Gonzalez Prada, edited by Luis Alberto Sanchez. It includes essays, speeches, and polemical writings drawn from two of Prada's only books of prose published during his lifetime, Paginas Libres and Horas de Lucha; in addition to unpublished manuscripts and works previously printed in newspapers and magazines. These writings reveal his most important thoughts on the subject of anarchism, social inequality, indigenous culture, philosophy, and language. Translated into English for the first time, Prada's forceful and persuasive words are gathered here under the thematic headings "Peruvian Problems," "Anarchy," and "Philosophical, Literary, and Linguistic Problems.""--Jacket